Analysis of Istitha'ah Achievement at the Center for Hajj and Umrah Health Integrated Services (P2TKHU) RS Hajj Hospital Jakarta - Hasan Lutfi, Syarief; Rumengan, Grace; AhdunTrigono (International Journal of Psychosocial Rehabilitation, 2020)
Hajj is a physical worship that require preparation before departure. Improving the ability of the candidate jama`ahendurans Hajj and Umrah performed as istitha`ah requirements. Preventive care is implemented in an integrated and multidisciplinary in Rs. Haji as a featured service program, of which Rs Hajj hospital for Kemenag as responsible mandate of Law no. 8 2017 in lieu of Law no. 13 of 2008 (Kemenag responsible for the care, protection and health of the pilgrims). The goal is to determine the attainment analysis Istithaah in Health Integrated Service Center of Hajj and Umrah (P2TKHU) Haji Hospital Jakarta 2019. The research material was Questionnaires pilgrims in P2TKHU months from May to July 2019. As for how that is done through the first stage with a cross-sectional study of the 96 respondents jama`ah P2TKHU pilgrim Haji Hospital Jakarta.Based on the results obtained from 96 samples of respondents that istithaah achieved in P2TKHU RS. Haji Jakarta as many as 62 people (64.6%), while the istithaah not been achieved in P2TKHU RS. Haji Jakarta as many as 34 people (35.4%). Hajj is a physical worship, where pilgrims must have comprehensive abilities as defined istitha'ah include badaniyah / jasmaniyah (health), amniyah (security), Maliyah (material). From all the variables tested multivariate data analysis that the most dominant variable is related to the achievement Istithaahemphaty with OR = 3.395.Based on the results obtained from 96 samples of respondents the istithaah achieved in P2TKHU RS. Haji Jakarta as many as 62 people, while the istithh not been achieved in P2TKHU RS. Haji Jakarta as many as 34 people. Empathy is a very significant relationship compared with other variables (tangible, reliability, responsivenes, assurance). Hajj is a physical worship, where pilgrims must have comprehensive abilities as defined istitha'ah include badaniyah / jasmaniyah (health), amniyah (security), Maliyah (material). And correlates with integrated services.